Modelling Media Entrepreneurship in Social Media: SEM and MLP-ANN Approach (2019)
The present paper addresses the need for a quantitative model for media entrepreneurship. In a framework of social media entrepreneurship that is presented by khajeheian (2013), 23 factors are introduced and categorized in five groups. Four groups of enterprise, resources, strategy and product are controllable and infrastructure is the uncontrollable group. In the current research, these groups are considered as variables and factors are used as measures. In a survey 305 Iranian students responded a questionnaire. SEM and MLP-ANN used for analysis. Results show that resources are on the highest rank, strategy and infrastructure are placed as 2nd and 3rd and enterprise and product placed at the lowest rank. This model can be used as a foundation for developing more quantitative researches in the subject of media entrepreneurship.